Combined Continuous Resin Adsorption and Anaerobic Digestion of Olive Mill Wastewater for Polyphenol and Energy Recovery - Chaimaa Hakim; Mounsef Neffa; Abdessadek Essadek; Audrey Battimelli; Renaud Escudie; Diana García-Bernet; Jérôme Harmand; Hélène Carrère (Energies, 2025)
Olive mill wastewater (OMWW) has high energetic potential due to its organic load, but its complex composition and toxicity limit efficient energy recovery. This study proposes an innovative integrated process combining continuous resin adsorption with anaerobic digestion to detoxify OMWW and recover renewable energy simultaneously. It studies the recovery of polyphenols, methane production, and substrate degradation efficiency using resin column bed heights (C1: 5.7 cm, C2: 12.1 cm, C3: 18.5 cm), as well as kinetic modeling of organic matter degradation. Adsorption reduced chemical oxygen demand (COD) by up to 80% and polyphenols by up to 64%, which significantly improved substrate biodegradability from 34% to 82%, corresponding to a methane yield of 287 mL CH4/g COD. Organic matter was fractioned into rapid (S1), moderate (S2), and slow (S3) biodegradable fractions. The highest degradation kinetics was C3, with methane production rates of K1 = 23.86, K2 = 2.47, and K3 = 2.92 mL CH4/d. However, this condition produced the lowest volumetric methane production due to excessive COD removal, including readily biodegradable matter. These results highlight the importance of optimizing the adsorption step in order to find to a balance between detoxification and energy recovery from OMWW, thus supporting the principles of circular economy and promoting renewable energy production.